2017
DOI: 10.1097/01.aog.0000514716.73888.2a
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Depression and Anxiety — Implementing Screening and Response Protocols [6N]

Abstract: INTRODUCTION: Perinatal mood and anxiety disorders are the most common pregnancy complications, and are associated with adverse maternal, infant and child outcomes. Recognizing this, the Council on Patient Safety in Women's Healthcare developed an evidence-based safety bundle to establish a standard of care for these disorders that is relevant to every woman in every clinical setting. Its objective was to outline how to implement current recommendations at the practice level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Routine, standardized screening in pregnancy for mental health disorders is recommended in high-income countries, including the United Kingdom [13], the United States [14], and Australia [1]. Implementation of such processes requires consideration of each setting [15]. In Australia, these recommendations have not been well implemented because of significant barriers at both the level of the service and the individual.…”
Section: Introductionmentioning
confidence: 99%
“…Routine, standardized screening in pregnancy for mental health disorders is recommended in high-income countries, including the United Kingdom [13], the United States [14], and Australia [1]. Implementation of such processes requires consideration of each setting [15]. In Australia, these recommendations have not been well implemented because of significant barriers at both the level of the service and the individual.…”
Section: Introductionmentioning
confidence: 99%
“…A gravidez é um momento de vulnerabilidade para o início ou recaída de doença mental (1) . Neste período, a depressão é o transtorno psiquiátrico mais prevalente, com sintomas que variam de leves a graves (2)(3) . Revisão sistemática de estudos realizados em países desenvolvidos e de baixa renda relatou prevalência de depressão pré-natal na faixa de 15,6% a 31,1% (1) .…”
Section: Introductionunclassified
“…Pregnancy is a time of vulnerability for the onset or relapse of mental illness (1) . In this period, depression is the most prevalent psychiatric disorder, with symptoms ranging from mild to severe (2)(3) . A systematic review of studies conducted in developed and low-income countries reported a prevalence of prenatal depression in the range of 15.6% to 31.1% (1) .…”
Section: Introductionmentioning
confidence: 99%